Chronic pulmonary arterial hypertension in children - Bruwer, A.D.; Brown, S.C. (SA Heart Journal, 2017)
Pulmonary arterial hypertension, although not common in children, has a poor prognosis. The definition, modern classification, causes and pathogenesis are discussed. Although the pathogenesis is complex and not completely understood, we now have a better understanding of it. The mechanisms and structural alterations underlying vasoconstriction of the pulmonary vasculature, remodelling of the pulmonary vessel wall and progressive obstruction and obliteration of the vascular bed with thrombosis are set out with the different mediators involved. Diagnosis can be difficult and a high level of suspicion is necessary to achieve an early diagnosis. The approach to management includes a methodical workup. The medication options discussed are based on an understanding of the pathophysiology.